Kedudukan Advokat Guna Membantu Lembaga Penegak Hukum Dalam Pelaksanaan Hukum Pidana di Indonesia - Ibnu Ilham Pratama; Sahrizal Rambe; Fauziah Lubis (Fakultas Syariah IAIN Laa Roiba Bogor, 2023)
The position of an advocate is written in the Law of the Republic of Indonesia Number 18 of 2003. An advocate is a profession that is well known in the field of law. However, the existence of Article 5 paragraph 1 (one) does not yet provide an explanation of the form of meaning as a law enforcer. Particularly in the role of elements in law enforcement in the criminal justice system in Indonesia, the method used in this research is the normative juridical method which aims to explore and study various laws and regulations, discuss the position of an advocate and know the responsibilities of an advocate in assist law enforcement agencies in the implementation of criminal law in Indonesia. Data analysis in this study was carried out using descriptive qualitative. Based on the research, it was concluded that the role of lawyers in the Indonesian criminal justice system: The role of advocates in the Indonesian legal system is recognized as the police is the same as other law enforcement professions such as police, prosecutors and judges according to Law Number 18 of 2003 concerning Law, therefore it is expected to practice law in a position equal to upholding the law and based on professionalism. About justice and upholding the truth. The duties, obligations, attitudes and responsibilities of an advocate as a police officer are all contained in the code of ethics of the legal profession which forms the basis of his practice. Keyword: Position, advocate, criminal law